Evolution of the approaches toward grading and classifying chronic changes in the renal allograft: Banff classification updates III - Mubarak,Muhammed (2014)
Currently, the most challenging problem in the field of renal and other solid organ transplantation is the development of chronic progressive sclerosing changes in the allograft. These occur almost uniformly in all renal allografts at a rate of 2-4% per year. In addition, such changes are also quite prevalent in well functioning grafts, as revealed by protocol biopsies. The chronic changes involve all the four components of the renal graft parenchyma, i.e., the glomeruli, blood vessels, tubules and interstitium. Among these, the glomerular and vascular changes are helpful in defining the causes of chronic changes, especially chronic rejection, but are more prone to sampling error, notably the blood vessels, whereas the tubulo-interstitial changes are less specific. However, because the later are less prone to sampling error, these are used for grading the severity of chronic changes in the Banff formulation. The identification, classification and grading of not only the acute but also the chronic changes is of vital importance in guiding the management and predicting the long-term graft outcome of renal transplant recipients. Banff has addressed the issue of chronic changes in detail in its first formulation, as well as its subsequent modifications. However, the magnitude of changes in this category that have occurred over the last two decades is less than that observed in the categories of antibody-mediated and T-cell-mediated rejections. This review describes in detail the changes that have taken place in the category of chronic allograft damage, as the original Banff classification has undergone updates regularly in the last two decades